Shaft part clamping tool wide in application range - JIANG RONGBIN; ZHUANG SHANSHAN (2022)
The utility model discloses a shaft part clamping tool wide in application range, and particularly relates to the field of clamping tools, the shaft part clamping tool comprises a first seat plate and a second seat plate, a first double-spiral screw is in threaded connection between the first seat plate and the second seat plate, the upper surface of the first seat plate and the upper surface of the second seat plate are both provided with adjusting blocks through fixing studs, and the first double-spiral screw and the second double-spiral screw are in threaded connection. The side edges of the two adjusting blocks are both in threaded connection with face clamping blocks, the opposite surfaces of the two adjusting blocks are both fixedly connected with connecting columns, and the middles of the ends of the connecting columns are rotationally connected with second double-spiral screws through bearings. By arranging the surface clamping block and the end clamping block, two different part clamping modes are ga